1973
DOI: 10.1111/j.1365-246x.1973.tb02379.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and Heat Flow in a Volcanic Rift Zone, with Application to Iceland

Abstract: A kinematic model of a volcanic rift zone, based on plate tectonics concepts of crustal accretion, is presented. Quantitative relationships between observable parameters of the model are tested by a comparison with estimates from Iceland of the rate of production of extrusive rocks by eruptions, the width of the volcanic zone, the drift velocity of the lithospheric plates, the regional dips of the flood basalts and the rate of increase of dyke volume fraction with depth in the eastern Iceland lava pile.Approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(115 citation statements)
references
References 29 publications
3
111
1
Order By: Relevance
“…The stratigraphy of the seaward-dipping reflector wedge is produced by applying the Palmason (1973Palmason ( , 1980 kinematic model for Icelandic crust as shown by Mutter et al (1982). However, we document an asymmetry of marginal features created during initiation of opening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stratigraphy of the seaward-dipping reflector wedge is produced by applying the Palmason (1973Palmason ( , 1980 kinematic model for Icelandic crust as shown by Mutter et al (1982). However, we document an asymmetry of marginal features created during initiation of opening.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Mutter et al (1982) invoked an igneous sequence formed subaerially during the earliest phase of seafloor spreading. They applied the model of subaerial crustal accretion developed for Iceland by Walker (1964) and Palmason (1973). Noting that the dipping reflectors were located landward of anomaly 23 and their relationship with an opaque, smooth acoustic basement surface along the margins of the Norwegian-Greenland Sea, Eldholm et al (1979) suggested that the dipping wedges reflect intense volcanic activity during early seafloor spreading, possibly associated with migration of the plate boundary.…”
Section: V0ring Plateau Marginal Highmentioning
confidence: 99%
See 1 more Smart Citation
“…These events also produced the only lava flows that extend beyond the limits of the active volcanic zones. Therefore, in accordance to the Pálmason (1973) spreading model, they have the highest potential for preservation within the Icelandic stratigraphic succession of the modern volcanic products. As such, they may represent the rate by which lava is added to the plateau basalt pile of Iceland, but it is clear from the Tertiary succession, which for example includes numerous central volcanoes, that volcanic structures with distribution limited to the active volcanic zones are also incorporated into the long-term stratigraphic record (e.g.…”
Section: Magma Output: Volume Of Erupted Magmamentioning
confidence: 99%
“…Geothermal wells and hot springs exist throughout the southern lowlands. They result from the high regional geothermal gradient, that ranges from 60°C/km to 150°C/km [Palmason, 1973]. Theregion east of the anticline has a similar geothermal gradient but no geothermal areas or boreholes are available for radon monitoring.…”
Section: Geology and Flow Of Groundwatermentioning
confidence: 99%